2016
DOI: 10.1111/pbi.12639
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions, cellular components and gene regulatory basis underlying pod length variations in cowpea (V. unguiculata L. Walp)

Abstract: SummaryCowpea (V. unguiculata L. Walp) is a climate resilient legume crop important for food security. Cultivated cowpea (V. unguiculata L) generally comprises the bushy, short‐podded grain cowpea dominant in Africa and the climbing, long‐podded vegetable cowpea popular in Asia. How selection has contributed to the diversification of the two types of cowpea remains largely unknown. In the current study, a novel genotyping assay for over 50 000 SNPs was employed to delineate genomic regions governing pod length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 38 publications
6
78
1
Order By: Relevance
“…In subsp. sesquipedalis, QTL for DRTs including pod shattering, pod length and flower color have been also reported (Kongjaimun et al 2012;Suanum et al 2016;Xu et al 2011;Xu et al 2017). However, to date no candidate genes underlying domestication traits have been reported in cowpea.…”
Section: Introductionmentioning
confidence: 99%
“…In subsp. sesquipedalis, QTL for DRTs including pod shattering, pod length and flower color have been also reported (Kongjaimun et al 2012;Suanum et al 2016;Xu et al 2011;Xu et al 2017). However, to date no candidate genes underlying domestication traits have been reported in cowpea.…”
Section: Introductionmentioning
confidence: 99%
“…The genotypes of the 119 RILs were retrieved from Xu et al (2017), where 7,988 high quality SNP data were acquired by using the Cowpea iSelect Consortium Array which represents a publicly accessible resource for screening 51 128 SNPs. The Cowpea iSelect Consortium Array is available from Illumina (Illumina Inc., San Diego, CA, USA; http://www.illu mina.com/areas-of-interest/agrigenomics/ consortia.html).…”
Section: Dna Extraction and Genotype Identificationmentioning
confidence: 99%
“…Lush et al also reported that duration of photosynthetic activity has increased after cowpea is domesticated [11]. Transcriptomic analysis suggests that sugar metabolism, gibberellin and nutritional signalling are involved in pod length regulation in cowpea [10].…”
mentioning
confidence: 97%
“…QTL co-localization analysis has helped understanding the co-domestication of different traits, either favorable or unfavorable for vegetable use. For example, QTLs controlling pod number per pod and pod length are co-localized but in different directions in terms of effect [10][11][12], explaining the paradox of pod quality and yield that has long been faced by cowpea growers [13][14]. Co-localizations of QTLs governing pod tenderness and pod length were also reported, which well explained why cowpea varieties with longer pods are often more soft [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation